Assesment of patient's perspective on treatment free remission in CML: A Turkish multicenter cohort - Mutlu, Yaşa Gül; Güvenç, Birol; Serin, İstemi; Balık Aydın, Berrin; Alacacıoğlu, İnci; Güven, Serkan; Sevindik, Ömür Gökmen (American Society of Hematology, 2022)
Treatment free remission (TFR) is one of the main goals of therapy in Chronic Myeloid Leukemia (CML). Patient perspective and expectations have an indicative effect on discontinuation decisions. We analyzed 116 CML patients' perspective on TFR and factors that associated with willingness for tyrosine kinaz inhibitor (TKI) discontinuation from four different center in Turkey based on a national survey. Patients in our cohort had 7.8% awareness of TFR and after brief information willingness to attempt TFR has been reached to 58.9% in all population. Shorter disease duration was associated with enhanced willingness to attempt discontinuation in multivariate analyses (p=0.031). Most common patient related limitation for TKI discontinuation decision was anxiety about disease relaps and TKI resistance. Even disease relaps in TFR means molecular and detectable with close monitoring, patients still had considerable concerns about TKI discontinuation.
Keywords: Turkish Multicenter Cohort; CML; Free Remission